Analysis of the Utilization of Learning Management System (LMS) as Learning Media for Informatics Education Students - Hamzah, Moh. Syukron; Sogen, Maria Magdalena Beatrice; Liu, Argi Hartanto; Tuan, Fransiskus Xaverius (JUPE : Jurnal Pendidikan Mandala, 2025)
Amidst the advancement of educational technology, the utilization of learning management systems (LMS) still faces a number of obstacles, especially in terms of student perceptions regarding ease of use, feature functionality, and the level of satisfaction felt during the learning process. This study aims to evaluate in depth the utilization of Learning Management Systems (LMS) as the main tool in the learning process of students in the Informatics Education Study Program, Citra Bangsa University. The main problems studied in this study include student perceptions of aspects of ease of use, interface appearance, completeness of features, interactivity, learning effectiveness, and level of satisfaction in using LMS. The research methodology applied is quantitative descriptive, with an instrument in the form of a questionnaire distributed to 30 students from semesters 2, 4, and 6. The findings show that the majority of students gave positive assessments, especially in terms of ease of use (86.7%), interface appearance (90%), completeness of features (83.3%), interaction and collaboration (86.6%), and effectiveness in understanding the material (83.3%). However, the level of satisfaction and preference for LMS is still at 70%, indicating a need for further development. Thus. LMS can be categorized as an effective and feasible platform to be developed in the context of digital learning in higher education.